An Australian model of the First 1000 Days: an Indigenous-led process to turn an international initiative into an early-life strategy benefiting indigenous families. (2016) - Ritte, R.; Panozzo, S.; Johnston, L.; Agerholm, J.; Kvernmo, S. E.; Rowley, K.; Arabena, K.
Abstract : Internationally, the 1000 days movement calls for action and investment in improving nutrition for the period from a child's conception to their second birthday, thereby providing an organising framework for early-life interventions. To ensure Australian Indigenous families benefit from this 1000 days framework, an Indigenous-led year-long engagement process was undertaken linking early-life researchers, research institutions, policy-makers, professional associations and human rights activists with Australian Indigenous organisations and families. The resultant model, First 1000 Days Australia, broadened the international concept beyond improving nutrition. The First 1000 Days Australia model was built by adhering to Indigenous methodologies, a recognition of the centrality of culture that reinforces and strengthens families, and uses a holistic view of health and wellbeing. The First 1000 Days Australia was developed under the auspice of Indigenous people's leadership using a collective impact framework. As such, the model emphasises Indigenous leadership, mutual trust and solidarity to achieve early-life equity.